Analisis Strategi Pengembangan Usaha Lemon (Citrus Limon L.) - Lumongga, Dumasari; Fathurrrohman, Yusuf Enril; Watemin, Watemin; Safitri, Rike Nur (Jurnal Sosial Ekonomi Pertanian, 2024)
Lemon is one of the horticultural commodities that has potential and is currently receiving priority for development. The aim of this research is to analyze internal factors and external factors, formulate alternative strategies, and determine strategic priorities that can be carried out in the lemon business (Citrus Limon L.) development strategy. The data analysis method used by researchers is IFE, EFE, IE, SWOT and QSPM matrix analysis. Based on the research results, 12 internal factors and 12 external factors were obtained in PT XYZ's lemon business. In the IE matrix, the results of comparing the total score values ​​from the IFE and EFE matrices show that the position of lemon business (Citrus Limon L.) is in cell V with coordinate values ​​2.42608; 2.71945. Looking at the position of PT XYZ's lemon business (Citrus Limon L.), 6 alternative strategies were produced in the SWOT matrix which can be carried out as steps in developing the lemon business (Citrus Limon L.). The analyze QSPM results show that there are 3 strategies that are priorities in developing  lemon business (Citrus Limon L.), namely: 1) Carrying out product development and offering products to new businesses/consumers; 2) Develop product marketing by maintaining economical selling prices to consumers; 3) Expanding the scope of market penetration through collaboration with government agencies, other companies and culinary businesses made from lemon. Keywords : lemons; development strategy; SWOT; QSPM.